Habitus and Cultural Capital Among Muslim Women: The Case of Women’s Empowerment in Nasyiatul Aisyiyah Gamping, Yogyakarta, Indonesia - Amanah, Siti Nur; Isroyan, Doni (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2024)
This article discusses the Muslim women’s empowerment movement carried out by Nasyiatul Aisyiyah Gamping, Yogyakarta, in the context of gender justice and various issues surrounding women, such as female scholars, women’s involvement in public spaces, and the cultural roles of women in society. The capital and habituation of Muslim women in this study are understood as the theoretical and practical implications of the women’s empowerment movement. This research uses a qualitative approach with a case study method of the Nasyiatul Aisyiyah Gamping women’s organization. The results show that the women’s empowerment movement within this organization is carried out through three main aspects: structural, cultural, and knowledge-based individual aspects. In the structural aspect, empowerment is reflected in the active involvement of women in organizational activities. In the cultural aspect, women play a role in various religious activities within the Gamping community. Meanwhile, in the individual aspect, empowerment is seen in the increased access of Muslim women to knowledge related to gender justice. Although this movement has become part of social transformation, there are still various challenges to face, both structurally and culturally. The patriarchal epistemology that remains deeply rooted in several elements of the leadership and the Gamping community presents obstacles that complicate the struggle to achieve gender justice, even at the local level. The empowerment and habituation efforts for Muslim women through Nasyiatul Aisyiyah Gamping remain a long-term endeavor that requires sustainable strategies.Abstrak: Artikel ini membahas gerakan pemberdayaan perempuan Muslim yang dilakukan oleh Nasyiatul Aisyiyah Gamping, Yogyakarta, dalam konteks keadilan gender dan berbagai isu yang mengitari perempuan, seperti ulama perempuan, keterlibatan perempuan di ruang publik, serta peran kultural perempuan dalam masyarakat. Modal dan habituasi perempuan Muslim dalam penelitian ini dipahami sebagai implikasi teoretis dan praktis dari gerakan pemberdayaan perempuan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus terhadap organisasi perempuan Nasyiatul Aisyiyah Gamping. Hasil penelitian menunjukkan bahwa gerakan pemberdayaan perempuan dalam organisasi ini dilakukan melalui tiga aspek utama: struktural, kultural, dan berbasis pengetahuan individu. Pada aspek struktural, pemberdayaan tercermin dalam keterlibatan aktif perempuan dalam kegiatan organisasi. Pada aspek kultural, perempuan berperan dalam berbagai aktivitas keagamaan di masyarakat Gamping. Sementara itu, pada aspek individu, pemberdayaan terlihat dari peningkatan akses perempuan Muslim terhadap pengetahuan terkait keadilan gender. Meskipun gerakan ini telah menjadi bagian dari transformasi sosial, masih terdapat berbagai tantangan yang harus dihadapi, baik secara struktural maupun kultural. Epistem patriarki yang masih mengakar dalam beberapa elemen kepengurusan dan masyarakat Gamping menjadi hambatan yang memperumit perjuangan mewujudkan keadilan gender, bahkan di tingkat lokal. Upaya pemberdayaan dan habituasi perempuan Muslim melalui Nasyiatul Aisyiyah Gamping tetap menjadi pekerjaan jangka panjang yang membutuhkan strategi berkelanjutan.